Alternative approach for managing pyometra in mares - Eduardo Prado; Alexandra Hartsell; Elizabeth Collar; Lex Baldwin; Daniel Prado; Tanner Drum; Colton Short; Paxton Parker; Lew Strickland; Tulio Prado (Clinical Theriogenology, 2026)
Two mares (varying in breed and age) were presented on separate dates after unsuccessful chronic pyometra treatment. Mares were assessed via transrectal ultrasonography; purulent material accumulation in the uterus was confirmed. Vaginal and cervical evaluation revealed cervical adhesion. Blunt debridement allowed access to uterus and uterine lavage treatment. Uterine infection was treated with intrauterine antibiotic infusions, based on culture and sensitivity results. A plastic tube was placed through the cervix and anchored into cervical caudal body using 2 knots of nonabsorbable suture in a horizontal pattern to maintain patency to allow healing. Pyometra was resolved and mares became clinically normal.